Effect of Acetaldehyde Intoxication and Withdrawal on NPY Expression: Focus on Endocannabinoidergic System Involvement - Plescia, Fulvio; Brancato, Anna; Marino, Rosa Anna Maria; Vita, Carlotta; Navarra, Michele; Cannizzaro, Carla (Frontiers in Psychiatry, 2014)
Acetaldehyde (ACD), the first alcohol metabolite, plays a pivotal role in the rewarding, motivational and addictive properties of the parental compound. Many studies have investigated the role of ACD in mediating neurochemical and behavioral effects induced by alcohol administration, but very little is known about the modulation of neuropeptide systems following ACD intoxication and withdrawal. Indeed the neuropeptide Y (NPY) system is altered during alcohol withdrawal in key regions for cerebrocortical excitability and neuroplasticity. The primary goal of this research was to investigate the effects of ACD intoxication and withdrawal by recording rat behavior and by measuring neuropeptide Y immunoreactivity in hippocampus and NAcc, two brain regions mainly involved in processes which encompass neuroplasticity in alcohol dependence. Furthermore, on the basis of the involvement of endocannabinoidergic system in alcohol and ACD reinforcing effects, the role of the selective CB1 receptor antagonist AM281 in modulating NPY expression during withdrawal was assessed. Our results indicate that: i) ACD intoxication induced a reduction in NPY expression in hippocampus and NAcc; ii) symptoms of physical dependence, similar to alcohol's, were scored at 12h from the last administration of ACD; iii) NPY levels increased in early and prolonged acute withdrawal in both brain regions examined. The administration of AM281 was able to blunt signs of ACD-induced physical dependence; to modulate NPY levels, and to further increase NPY expression during ACD withdrawal both in hippocampus and NAcc. In conclusion, the present study shows that complex plastic changes take place in NPY system during ACD intoxication and subsequent withdrawal in rat hippocampal formation and NAcc. The pharmacological inhibition of CB1 signaling could counteract the neurochemical imbalance associated with ACD, and alcohol withdrawal, likely boosting the setting up of homeostatic functional recovery.